Viver e envelhecer de professores no cotidiano escolar - Vargas, Hanidria Leticia Boscar (2016)
This work aimed to evaluate the impact of everyday school life in living and aging of teachers, considering the determinants of active aging and to identify how teachers seek healthy and being active in the process of living and aging. Therefore, we adopted a concept that included the family sphere, the workplace, public policies among other determinants that can change values and conceptions of life when it comes to age healthily. The method used was qualitative, exploratory and descriptive, wh ich made use of the focus group strategy for data collection. Participated in the investigation eleven te achers, characterized as gender, age, training, specialization, practice time in the profession and work experience in the municipal school. From that emerged from the discussions in the groups was constructed categories that express the impact of everyday school life in living and aging of teachers, such as physical environment, emerging challenges in school, the teacher at school: what role is this? Professional predominance of women and health signs. It was possible to identify that teachers have knowledge of the reality of public schools and the work environment influences the personal and professional life as well as in their actions of teaching and learning. If the working environment does not match the expectations of teachers, they feel that health is threatened by everyday circumstances, thus compromising the quality of work. It is considered important to have harmony between behavioral determinants, personal, social, economic, physical environment, and health to think about active aging and reducing the impact on live age teachers in the profession.